Upaya Guru dalam Meningkatkan Sikap Kesosialan Siswa - M. Bahri Mustofa; Fadia Ais; Dewi Citra Puspita Sari; Faradisa Putri Yani; Muhamad Hasan Bishri (Jurnal Pendidikan Guru Madrasah Ibtidaiyah Al-Amin, 2024)
This research discusses the role of education in developing students' potential which includes intellectual (cognitive), skills (psychomotor) and attitudes (emotional). Based on Law Number 20 of 2003 concerning the National Education System, education aims to shape students' personality, intelligence and noble morals. The main focus of the research is the importance of social attitudes that involve empathy, tolerance and cooperation in everyday life and the role of teachers in developing these attitudes. This research was conducted at SDS Raudhotul Ulum Bangil using deductive, observation and interview methods. The research results show that students' social attitudes, such as honesty, discipline, responsibility, politeness, caring and self-confience, are greatly influenced by the social environment, including family, school and society. Teachers play a significant role in instilling social attitudes through example, positive reinforcement, and punishment. Effective strategies include communication, group work, familiarization with religious values ​​and Pancasila, and giving awards. In conclusion, developing social attitudes through the active role of teachers can help students become individuals who are empathetic, responsible and contribute positively to society. This research provides additional insight into best practices in improving students' social attitudes and the factors that influence them.